Legal Consequences of Developer Default in Build-Share Agreements (Study Decision Number 39/Pdt.G/2016/Pn Tpg) - Pandu Ariza; Budiman Ginting; T.Keizerina Devi Azwar; Suprayitno; Hasim Purba; Mahmul Siregar (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the regulation of default in contract law according to the Civil Code, analyze the legal consequences of developer default in building share agreements in decision number 39/Pdt.G/2016/PN Tpg and analyze the legal analysis of District Court decision number 39/Pdt.G /2016/PN Tpg regarding building share agreement. The research method is normative juridical, which is descriptive analysis with data collection techniques of library research. The focus of the problem concerns the legal consequences of developer default in fulfilling achievements in the build-share agreement (Study Decision Number 39/Pdt.G/2016/Pn Tpg). Based on the research results, the act of breach of contract (Article 1243 of the Civil Code) has consequences for the aggrieved party's right to sue the party who committed the default to provide compensation so that by law it is hoped that no party will be harmed due to the breach of contract and non-fulfillment of the agreement due to negligence. (fault) debtor.